The Influence of the Hofmeister Bias and the Stability and Speciation of Chloridolanthanates on Their Extraction from Chloride Media. Issue 7 (9th November 2016) - Doidge, Euan D.; Carson, Innis; Love, Jason B.; Morrison, Carole A.; Tasker, Peter A.
ABSTRACT: The possibility of recovering rare earth elements from solutions containing their chloridometalate anions [LnCl x ] ( x −3)− via the process: LnCl x ( x −3)− + ( x − 3) L org + ( x –3)H + ⇌ [(LH) x −3 LnCl x ]org has been tested using 2-(1, 3-bis(hexylamino)-1, 3-dioxopropan-2-yl)-4, 6-di- tert -butylpyridine (PMA), tri- n- butylphosphate (TBP), and tri- n -octylamine (TOA), which are known to be strong extractants for transition metal chloridometalates. While DFT calculations indicate that the formation of the neutral assembly [(PMAH)3 LaCl6 ] in the gas phase is favorable, no uptake of La(III) from 6 M HCl by toluene solutions of PMA (or of TBP or TOA) was observed in solvent extraction experiments. Successful uptake of the [PtCl6 ] 2− dianion by PMA and the failure to extract the [IrCl6 ] 3− trianion under the same conditions indicate that the higher hydration energy of the latter makes transfer to the toluene solution less favorable and that this militates against extraction of La(III) chlorido complexes carrying charges of −3 or larger in which all the inner-sphere water molecules have been replaced. Computational results confirm literature observations that, in contrast to transition metal trications, formation of REE metalate anions such as [LnCl x ] ( x −3)− is not very favorable, particularly so for chloride, compared with nitrato or sulfato systems. Also, they indicate that the formation of outer-sphere assemblies such as [La(H2 O)9 ]· x Cl in which water ligands are retained in the inner sphere, H-bonded to anions, is more stable than inner-sphere complexes containing an equivalent number of anions. The high level of hydration of such species disfavors their transfer into nonpolar water-immiscible solvents. It is unlikely that recovery of [LnCl x ] ( x −3)− from acidic solutions can be achieved efficiently using currently available anion exchange extractants operating in a "pH-swing" process. Receptors giving very high binding energies to chloridolanthanates will be needed to offset the high dehydration energies required.